Municipal-private partnership — effective way of development of ambulatory urological assistance - Ashot R. Gevorkyan (Медицинский вестник Юга России, 2017)
Priority directions of improving the organization of work of the municipal outpatient urological service in the new economic conditions is the formation of an eff ective economic mechanism on the basis of the MPP principles in outpatient institutions providing urological assistance, an example of which is the development of the functional and organizational structure of the regional ACC model on the principles of the MPP.